Membaca Falsafah Tallu Lolona sebagai Sarana Eko-Misional Kontekstual Gereja Toraja Berdasarkan Kejadian 1:27-28 dan 2:15 - Exan Rerung , Alvary (Institut Agama Kristen Negeri Toraja, 2024)
This article discusses the problem of ecological crisis which is apparently caused by the moral problems of mankind. This also happened in Toraja because of the actions of some Torajans who no longer care about their environment. Floods occurred in various places due to overflowing rivers because they were used as garbage dumps. Drainage no longer functions properly to drain rainfall because it is filled with garbage that is dumped irresponsibly. In fact, environmental destruction according to Toraja culture is taboo because it affects many people. Through the literature study method, this article intends to read the philosophy of tallu lolona based on Genesis 1:27-28 and 2:15. The results of this reading can be used as a contextual eco-missionary tool for the Toraja Church to remind its congregation that both the Bible and Toraja culture prohibit environmental destruction. On the contrary, the Bible and Toraja culture command to protect and preserve the environment as the implementation of missio Dei for the world.Tulisan ini berbicara tentang masalah krisis ekologi yang ternyata disebabkan oleh masalah moral umat manusia. Hal ini terjadi juga di Toraja karena ulah sebagian orang Toraja yang tidak peduli lagi dengan lingkungannya. Terjadi banjir di berbagai tempat akibat sungai yang meluap karena dijadikan tempat pembuangan sampah. Drainase tidak lagi berfungsi dengan baik untuk mengalirkan curah hujan akibat dipenuhi sampah yang dibuang secara tidak bertanggung jawab. Padahal, perusakan lingkungan menurut budaya orang Toraja adalah hal yang tabu karena berdampak pada orang banyak. Melalui metode studi pustaka, tulisan ini hendak membaca falsafah tallu lolona berdasarkan Kejadian 1:27-28 dan 2:15. Hasil pembacaan ini bisa dipakai menjadi sarana eko-misional kontekstual bagi Gereja Toraja untuk mengingatkan warga jemaatnya bahwa baik Alkitab dan juga budaya orang Toraja melarang terjadinya perusakan lingkungan. Sebaliknya, Alkitab dan budaya orang Toraja memerintahkan untuk menjaga dan memelihara lingkungan sebagai pelaksanaan missio Dei bagi dunia.